2021
DOI: 10.3390/ijerph18147406
|View full text |Cite
|
Sign up to set email alerts
|

Coating with Hypertonic Saline Improves Virus Protection of Filtering Facepiece Manyfold—Benefit of Salt Impregnation in Times of Pandemic

Abstract: Recently, as is evident with the COVID-19 pandemic, virus-containing aerosols can rapidly spread worldwide. As a consequence, filtering facepieces (FFP) are essential tools to protect against airborne viral particles. Incorrect donning and doffing of masks and a lack of hand-hygiene cause contagion by the wearers’ own hands. This study aimed to prove that hypertonic saline effectively reduces the infectious viral load on treated masks. Therefore, a hypertonic salt solution´s protective effect on surgical masks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…These results were confirmed by the TCID 50 assay results showing that fewer virus particles were able to infect cells after having been in direct contact with the salt-coated fabrics. These findings are in line with those of previous studies that demonstrated the effects of salt deposition on the inner filter in surgical masks followed by influenza A/H1N1 virus inoculation 20 , and salt spraying on the outer layer of surgical masks and subsequent inoculation with a pig virus (transmissible gastroenteritis virus) 35 . However, there was no clear negative correlation between the salt concentrations on the fabrics and the viral genome copy numbers in cell cultures.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were confirmed by the TCID 50 assay results showing that fewer virus particles were able to infect cells after having been in direct contact with the salt-coated fabrics. These findings are in line with those of previous studies that demonstrated the effects of salt deposition on the inner filter in surgical masks followed by influenza A/H1N1 virus inoculation 20 , and salt spraying on the outer layer of surgical masks and subsequent inoculation with a pig virus (transmissible gastroenteritis virus) 35 . However, there was no clear negative correlation between the salt concentrations on the fabrics and the viral genome copy numbers in cell cultures.…”
Section: Discussionsupporting
confidence: 92%
“…In parallel to the salt dissolution/recrystallization hypothesis, we considered the possibility that salt residues dissolved during the virus collection step may also have contributed to viral deactivation because of the hypertonicity of the medium, as previously shown for airborne microorganisms 35 . To test this hypothesis, A/H3N2 virus particles were incubated directly in solutions of varying salt concentrations, from isotonicity to saturation, prior to their inoculation in the MUCILAIR cell cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these common features make the viruses virtually indistinguishable from a structural point of view, making TGEV an excellent surrogate model for the investigation of the dynamics and stability of CoV in general. In fact, TGEV has already been used as a model of SARS-CoV-1 and SARS-CoV-2, especially in studies of astringent environmental conditions for virions and in studies of sensitivity to biocidal agents [ 22 , 23 , 24 ]. However, these studies did not explore the structural damage of the virions.…”
Section: Introductionmentioning
confidence: 99%
“…Quan et al 2017) and pig Alphacoronavirus 1(Tatzber et al 2021) after deposition on a melt-blown material from disposable surgical masks. Here, we wanted to extend these ndings to a material suitable for the manufacture of reusable cloth masks(Konda et al.…”
mentioning
confidence: 99%